Determinasi Pola Istirahat dan Pengetahuan Terhadap Risiko Anemia pada Siswi SMK Assalam Kota Depok - Nurmadinisia, Rahmi; Anandhila , Zihan (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2025)
Anemia is a global health problem with a prevalence of 30% of the world's population, especially in developing countries. Factors that contribute to the high prevalence of anemia in adolescents include menstrual patterns, adolescent knowledge, diet and rest patterns. The study aims to identify risk factors for anemia in adolescents for further efforts by the health service/government to prevent anemia in adolescents. This study is an analytical observational study with a cross-sectional approach and a chi-square test design. This study was conducted in May 2024. The data for this study came from primary data, including respondent characteristics, anemia risk questionnaires, knowledge questionnaires and rest time duration. The population of this study was all 116 female students of grades X, XI, XII in 2024. The sampling technique used was total sampling. Based on the results of research on the factors that influence the risk of anemia in female students at SMK Assalam, Depok City that has been carried out, the percentage of anemia risk (60.3%), poor rest patterns (86.2%), low knowledge (62.9%) was obtained. Based on the results of the bivariate test, there is a relationship between rest patterns and the risk of anemia in female students of SMK Assalam, Depok City. However, there is no relationship between knowledge and the risk of anemia in female students at SMK Assalam, Depok City in 2024. The results of this study indicate the need for interventions that emphasize good rest patterns to reduce the risk of anemia in adolescents.